Tomatinase from Fusarium oxysporum f. sp. lycopersici Defines a New Class of Saponinases - Teresa Roldán-Arjona; Alonso Pérez-Espinosa; Manuel Ruiz-Rubio (Molecular Plant-Microbe Interactions, 1999)
Plants produce a variety of secondary metabolites, many of which have antifungal activity. Saponins are plant glycosides that may provide a preformed chemical barrier against phytopathogenic fungi. Fusarium oxysporum f. sp. lycopersici and other tomato pathogens produce extracellular enzymes known as tomatinases, which deglycosylate α-tomatine to yield less toxic derivatives. We have cloned and characterized the cDNA and genomic DNA encoding tomatinase from the vascular pathogen of tomato F. oxysporum f. sp. lycopersici. This gene encodes a protein (FoTom1) with no amino acid sequence homology to any previously described saponinase, including tomatinase from Septoria lycopersici. Although FoTom1 is related to family 10 glycosyl hydrolases, which include mainly xylanases, it has no detectable xylanase activity. We have over-expressed and purified the protein with a bacterial heterologous system. The purified enzyme is active and cleaves α-tomatine into the less toxic compounds tomatidine and lycotetraose. Tomatinase from F. oxysporum f. sp. lycopersici is encoded by a single gene whose expression is induced by α-tomatine. This expression is fully repressed in the presence of glucose, which is consistent with the presence of two putative CREA binding sites in the promoter region of the tomatinase gene. The tomatinase gene is expressed in planta in both roots and stems throughout the entire disease cycle of F. oxysporum f. sp. lycopersici.